Education mobility as a driving force for the coexistence, development and sustainability of Islamic Higher Education Institutions: The International Islamic University Malaysia’s Perspective - Mohd Ali, Hairuddin (2017)
Global Prominence (eighth shift), comprising internationalization and education mobility, is considered as one of the supreme key result areas (KRAs) in the Malaysian Higher Education Blueprint 2015-2025 goals. This paper focused and discusses about Education Mobility as one of the KRAs that will generate a driving force for the coexistence, development and sustainability for higher education institutions in 2020s from an academic perspective. The discussion starts with the introduction of several education management related theories such as educational strategic management theories, education internationalization theories, education mobility theories, education development theories and higher education institutions sustainability theories. Next, the paper introduces and discusses the application of those theories in International Islamic University Malaysia (IIUM) long term strategic planning. The paper ends with suggestions and recommendations for improvement of IIUM’s strategic planning effective implementation.